Effect of Apheresis for ABO and HLA Desensitization on Anti-Measles Antibody Titers in Renal Transplantation - Ulf Schönermarck; Teresa Kauke; Gundula Jäger; Antje Habicht; Thorsten Wendler; Joachim Andrassy; Markus Guba; Manfred Stangl; Michael Fischereder (Journal of Transplantation)
Desensitization strategies for ABO-incompatible renal transplants with plasma exchange (PE) or specific immunoadsorption (IA) decrease immunoglobulin levels. After recent measles outbreak and decreasing vaccination rates, we studied the impact of apheresis on anti-measles antibodies. Anti-measles antibodies were measured before desensitization, before transplantation and during followup in 12 patients with ABO incompatibility (2x PE only, 8x IA only, and 2x IA and PE) and 3 patients with donor-specific HLA antibodies (all PE). Patients received rituximab, IVIG, and standard immunosuppressive therapy. All patients had detectable anti-measles antibodies before desensitization (mean 3238 mU/l, range 560–8100). After 3–6 PE sessions, titers decreased significantly to 1710 mU/l (𝑃<0.05), in one patient to nondetectable values, while IA only maintained protective titers. After a median followup of 64 days, anti-measles antibodies returned to baseline in all patients. Immunity against measles was temporarily reduced by apheresis but remained detectable in most patients at time of transplantation. Desensitization maintains long-term protective immunity against measles.